The Drug Treatment Court Concept : The Jamaican Drug Courts - Haisley, Stephane Jackson (World Bank, Washington, DC, 2014)
The Drug Treatment Court (DTC) model was conceived out of the need to solve the numerous and intractable problems that drug related cases create for court systems. A DTC is generally seen as a court that deals specifically with offenders who have committed offenses while under the influence of drugs and provides an alternative to incarceration. DTCs make use of a multidisciplinary team involving judges, prosecutors, defense attorneys, probation officers, treatment providers, police officers, and educational and vocational experts. The criminal justice and health service systems join to provide drug-dependent offenders with the mechanisms to recover from drug addiction and lead a productive and crime-free life. The purpose of this paper is to explore the concept of DTCs. After providing an overview of the origins of the DTC, looking at its roots in the United States and Canada, the paper examines the foundation and present-day experiences of DTCs in Jamaica. It also refers to some efforts among various countries in the Western Hemisphere to monitor DTCs and evaluate their effectiveness. The paper concludes with a return to the achievements of DTCs in Jamaica and a brief look at the future of the DTC program worldwide.